Comparative techno-economic study of typically combustion-less hydrogen production alternatives. (12th March 2023) - Mehanovic, Dino; Peloquin, Jean-François; Dufault, Jean-François; Fréchette, Luc; Picard, Mathieu
Abstract: A techno-economic study is performed for a large scale combustion-less hydrogen production process based on Steam Methane Reforming (SMR). Two process versions relying on different renewable heat sources are compared: (1) direct solar heating from a concentrated solar power system, and (2) radiation from resistive electrical heaters (electric SMR). Both processes are developed around an integrated micro-reactor technology, incorporating in a monolithic block most sub-processes needed to perform SMR. A baseline techno-economic scenario with low-cost feedstock and electricity, priced at $4/MMBtu and $0.04/kWh respectively, results in an LCOH of $2.31/kgH2 for solar SMR and $1.59/kgH2 for electric SMR. Results further show that solar SMR is currently more attractive economically than electric SMR coupled with distributed wind power systems, but electric SMR is more favourable in the long term due to the expected future improvements in the LCOE and capacity factor of wind power systems. Graphical abstract: Image 1 Highlights: Solar and electric SMR processes using integrated micro-reactors are presented. Grid-connected electric SMR has a prohibitive CO2 avoidance cost in most jurisdictions. A best-case scenario for grid-connected electric SMR has an LCOH of $1.59/kgH2 . The LCOH predicted for future wind-powered electric SMR is below $2/kgH2 . The LCOH of future solar SMR remains above $2/kgH2 .